Self-oscillatory device for vibration tests - Bozhko, A.E.; Polishchuk, O.F. (Проблемы прочности, 1985)
The present article suggests a method of controlling the resonance frequency of a mechanical oscillating system ensuring the diversity spacing of the resonance frequencies of the oscillator and of the tested structure, and it examines a self-oscillatory device which puts this method into practice.